Assessing the effect of urban digital infrastructure on green innovation: mechanism identification and spatial-temporal characteristics - Chengming Li; Meiyu Wen; Shaoxiang Jiang; Huaxing Wang (Humanities & Social Sciences Communications, 2024)
Abstract Under the background of digitization and greening in China, digital infrastructure offers new opportunities for developing green innovation. This paper investigates the effect of digital infrastructure on urban green innovation using panel data from 285 Chinese prefecture-level cities between 2011 and 2020, and explains the mechanism and its spatial-temporal dynamic effect. The results demonstrate that digital infrastructure promotes urban green innovation. Talent agglomeration, R&D investment increase, and industrial structure upgrading are crucial channels. Furthermore, depending on a city’s size, human capital, environmental regulations, and financial subsidies, digital infrastructure contributes to urban green innovation differently. Also, there is not only a positive spatial spillover effect of digital infrastructure but a threshold effect that presents a nonlinear trend of rising marginal effect. This study provides a new perspective for promoting digital infrastructure and urban green innovation, which makes a difference in facilitating its high-level development collaboratively.